Effect of Dietary Fibre Fractions on In Vitro Digestibility of Rapeseed Napin Proteins - Joehnke Marcel Skejovic; Sørensen Susanne; Bjergegaard Charlotte; Markedal Keld Ejdrup; Sørensen Jens Christian (Polish Journal of Food and Nutrition Sciences)
Protein digestibility may be influenced by the presence of dietary fibre affecting the nutritional quality of a feed or food product. This study investigated the interplay between rapeseed (Brassica napus L.) protein and fibre constituents separated by industrially scalable pilot plant processing and recombined in mixed samples. Total dietary fibre (TDF) fractions were isolated from rapeseed hulls (TDF-RH) and purified rapeseed embryo fibres (TDF-RE). The effect of TDF sources on in vitro protein digestibility (IVPD) of a rapeseed protein concentrate rich in napin proteins (RP2) was assessed at three inclusion levels (200, 333, and 500 mg/g DM) using a sequential transient proteolysis by pepsin (1 h) and pancreatin (1 h). The IVPD of RP2 was dose-dependently decreased upon addition of hull fibres at all inclusion levels (8.9-26.6%; P<0.05), whereas the effect of embryo fibres was of a markedly lower magnitude and only significant at the medium to high levels (7.3-8.9%; P<0.05). These results demonstrated that TDF fractions obtained from rapeseed differentially affect the protein digestibility of rapeseed napin proteins depending on the fibre source and inclusion level.